Evaluasi Capability Level Infrastruktur Jaringan Teknologi Informasi PT XYZ Menggunakan COBIT 2019 - Fahreza, Fahreza; Soewito, Benfano (Progresif: Jurnal Ilmiah Komputer, 2024)
PT XYZ is a telecommunications industry company that is undergoing digital transformation. However, in the process, there are several problems that pose risks such as the use of end-of-sale/life devices, the complexity of data exchange, and the lack of centralization of network devices. When undergoing digital transformation, PT XYZ can use Control Objectives for Information and Technology (COBIT 2019) as a reference system in assessing governance. Research data comes from telecommunications companies in Indonesia to measure the level of information technology governance capability using COBIT 2019 in the align, plan, organize (APO) APO02, APO03, APO04, build, acquire, implement (BAI) BAI01, BAI02, BAI04, and delivery, service, support (DSS) DSS01, and DSS02 domains. The results of the study show that management objectives APO02, APO03, APO04, BAI01, BAI02, BAI04, DSS01, and DSS02 have a low level of capability with levels namely APO02 level 3, APO03 level 1, APO04 level 3, BAI01-BAI02, and BAI04 level 1, DSS01, and DSS02 level 5 with an average value of the overall management objective is level 3 (defined process). Keywords: COBIT 2019 Framework; IT Governance; Capability Level; Telecommunication Industry Â AbstrakPT XYZ merupakan perusahaan industri telekomunikasi yang sedang melakukan transformasi digital. Namun, dalam proses tersebut terdapat beberapa masalah yang menimbulkan risiko seperti penggunaan perangkat end-of-sale/life, kompleksitas pertukaran data, dan kurangnya sentralisasi perangkat jaringan. Saat melakukan transformasi digital, PT XYZ dapat menggunakan Control Objective for Information and Technology (COBIT 2019) sebagai sistem acuan dalam menilai tata kelola. Data penelitian bersumber dari perusahaan telekomunikasi di Indonesia untuk mengukur tingkat kapabilitas tata kelola teknologi informasi menggunakan COBIT 2019 pada domain align, plan, organize (APO) APO02, APO03, APO04, build, acquire, implement (BAI) BAI01, BAI02, BAI04, dan delivery, service, support (DSS) DSS01, dan DSS02. Hasil penelitian menunjukkan management objektif APO02, APO03, APO04, BAI01, BAI02, BAI04, DSS01, dan DSS02 memiliki tingkat kapabilitas rendah dengan level yaitu APO02 level 3, APO03 level 1, APO04 level 3, BAI01-BAI02, dan BAI04 level 1, DSS01, dan DSS02 level 5 dengan nilai rata-rata keseluruhan management objective adalah level 3 (defined process).Kata kunci: COBIT 2019 Framework; IT Governance; Capability Level; Telecommunication Industry Â